Predictors of early discharge after transcatheter aortic valve implantation: insight from the CoreValve ClinicalService. Issue 7 (July 2022) - Angelillis, Marco; Costa, Giulia; Giannini, Cristina; Fiorina, Claudia; Branca, Luca; Tamburino, Corrado; Barbanti, Marco; Gorla, Riccardo; Casenghi, Matteo; Bruschi, Giuseppe; Merlanti, Bruno; Montorfano, Matteo; et al.
Abstract : Aims: The aim of this study was to minimize the procedure, and reduce the length of hospital stay (LoS) is the future objective for transcatheter aortic valve replacement (TAVI). Aims of the study are to identify procedural and electrocardiographical predictors of fast-track discharge in patients who underwent TAVI. Methods: Patients treated with TAVI included in the One Hospital ClinicalService project were categorized according to the LoS. 'Fast-Track' population, with a postprocedural LoS less than or equal to 3 days, was compared with the 'Slow-Track' population with a postprocedural LoS greater than 3 days. Results: One thousand five hundred and one patients were collected. Despite single baseline characteristics being almost similar between the two groups, Slow-Track group showed a higher surgical risk ( P  < 0.001). Patients in the Slow-Track group were more frequently treated with general anaesthesia ( P  = 0.002) and less frequently predilated ( P  < 0.001) and received a lower amount of contrast media. No difference between Slow-Track and Fast-Track patients was observed at 30 days in death and in cardiovascular rehospitalization. In the multivariable analysis, STS score of at least 4% [odds ratio (OR): 1.64; P  = 0.01], general anaesthesia (OR: 2.80; P  = 0.03), predilation (OR: 0.45; P  < 001), NYHA 3–4 at baseline (OR: 1.65; P  = 0.01), AVB I/LBBB/RBBB onset (OR: 2.41; P  < 0.001) and in-hospital new PM (OR: 2.63; P  < 0.001) were independently associated with a higher probability of Slow-Track. Conclusion: Fast-Track patients were safely discharged home showing no difference in clinical outcomes after discharge up to 30 days compared with the Slow-Track group. The STS score, general anaesthesia, NYHA 3--4 at baseline, in-hospital onset of conduction disturbances and new PM implantation after TAVI turned out to be predictors of Slow-Track.